The Effect of Guided Question in Enhancing The Students’ Writing Skill - Andhiny Angelia Vitriani; Amzah (Institut Agama Islam Negeri Parepare, 2020)
Andhiny Angelia Vitriani, 2020. The Effect of Guided Question in Enhancing The Students’ Writing Skill at the Second Grade of SMPN 1 Parepare (Supervised by Amzah and Mujahidah). This research was aimed to find out the effect of guided question to enhancing the students’ writing skill at the second grade of SMPN 1 Parepare. The purpose of this research was to know is guided question is effective to to enhance students’ writing skill and to know how students’ achievement in writing skill after taught by using guided question. This research took the second grade of SMPN 1 Parepare with 37 students as sample. This research was classified as quantitative research, where the instrument this research were writing test consist pre-test and post-test . The sampling technique of this research was cluster sampling. In this research used pre-experimental design with one group pre-test and post-test The researcher found that guided question was effective to enhance students writing skill, the students were able to show a sign progress especially: well began to construct sentences, showed a fairly good link between topic and whole content, and, showed a fairly good connected between sentences each other. Based on the calculation, the result of the data analysis by using t-test showed the value of t-test (to) was higher than ttable (tt), to > tt = (11.54 > 1.69) in significant degree of 0.05% (5%). It means that the Alternative Hypothesis (Ha) was accepted and the Null Hypothesis (Ho) is rejected. In conclusion, There is significant effect of Guided Question to enhance student’s writing skill or Guided Question Technique was effective to enhance students’ wrting skill. Keywords: Teaching Writing Skill, Guided Question